Ectopic first pregnancy treated by methotrexate versus salpingectomy—Maternal and perinatal outcomes in a subsequent pregnancy: A retrospective study. Issue 3 (8th August 2022) - Levin, Gabriel; Ohayon, Aviran; Weissbach, Tal; Burke, Yechiel Z.; Meyer, Raanan
Abstract: Objective: To study obstetric outcomes of a second pregnancy among women with a first ectopic pregnancy (EP) treated with methotrexate compared with laparoscopic salpingectomy. Methods: A retrospective cohort study including all women with a first EP and a following pregnancy that concluded by delivery at ≥24 weeks of gestation between March 2011 and April 2021. Second pregnancy outcomes were compared between women treated with methotrexate and those treated with salpingectomy in their first pregnancy. Results: Overall, 125 women were included, of which 64 (51.2%) were treated with methotrexate and 61 (48.8%) were treated with salpingectomy. In women treated with salpingectomy, the proportion of women conceiving by in vitro fertilization and those with measured gestational sac diameter or β‐subunit human chorionic gonadotropin was higher. The proportion of women conceiving by in vitro fertilization in their second pregnancy was higher in the salpingectomy group (55.2% versus 18.0%, P < 0.001). All maternal and neonatal outcomes were similar in both groups. The rate of low birth weight < 2500 g was 7.8% in the methotrexate group versus 18% in the salpingectomy group ( P = 0.111). Conclusion: Maternal and neonatal outcomes of a second pregnancy among women treated for EP in their first pregnancy are similar in women treated by methotrexate and those treated by salpingectomy. Synopsis: The method of treatment for a first ectopic pregnancy is not associated with maternal and neonatal outcome in the following delivery.